EXPERIMENTAL INVESTIGATION OF R600A REFRIGERANT FLOW INSIDE ADIABATIC CAPILLARY TUBE - Apaydin, Tolga; Heperkan, Hasan (YILDIZ TECHNICAL UNIV, 2016)
Capillary tubes are often used as an expansion component in the refrigeration systems of household refrigerators. During the flow of the refrigerant inside the capillary tube, due to pressure loss of the refrigerant, the refrigerant starts boiling and towards the end of the capillary tube, different types of two-phase regimes occur. Therefore; the refrigerant flow inside the capillary tube is a complex phenomenon and there are many experimental and numerical studies analyzing this refrigerant flow. However; in literature there are hardly any experimental studies analyzing refrigerant flow in small scale refrigeration systems using isobutane (R600a) as the refrigerant. In this study, the two-phase flow regimes of the R600a refrigerant inside a vertical adiabatic capillary tube with 0.80 mm inner diameter, under different condensation pressures subcooling degrees and capillary tube lengths, are recorded via high-speed camera; and the effects of different parameters on refrigerant mass flow are analyzed. The boundary conditions for the condensation pressure, subcooling degree and capillary tube length are determined in accordance with a small scale refrigeration system.
Keywords: Capillary tube; isobutane; two-phase flow; flow visualization; Engineering